Trusting banks in China - Zuzana Fungáčová; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
Trust in banks is essential to financial system effectiveness. This study examines the determinants of trust in banks in China. Using the most recent wave of the World Values Survey, which included information on trust in banks from the survey in China in 2012, we perform ordered logit estimations to investigate the potential influence of a large set of individual and provincial indicators on trust in banks. We observe the influence of certain sociodemographic indicators. Membership in the Communist Party and living in a rural area are negatively associated with trust in banks. Age and satisfaction with financial situation contribute to higher trust in banks, while being married and having a higher level of education tend to lower trust in banks. Access to information regardless of the type of media disseminating the information newspapers, television, internet) seem to have no impact on trust in banks. Economic values influence trust in banks. In particular, individuals who favor inequality as an incentive for individual effort or support an expanded government ownership role in the economy tend to trust banks more.
URN:NBN:fi:bof-201706061333
Keywords: G21; O16; P34; 330